The Concept of Internal IP Addresses System for NRENs - Tadevosyan, Robert N.; Petrosyan, Arthur S.; Petrosyan, Gurgen S. (Mathematical Problems of Computer Science, 2021)
This paper presents the concept of a new system of internal IP addresses proposed for use by National Research and Education Networks (NREN). Recently, various systems and services, have been actively developing, such as Wi-Fi, IP telephony, etc., for which it is necessary to ensure the security of streams, reducing the area of collisions, etc. The allocation of additional IP addresses in local networks makes it possible to realize all the abovementioned tasks and have the necessary reserve for future development. The concept is deployed in Academic Scientific Research Computer Network ofArmenia (ASNET-AM).